Molecular forms of prostate-specific antigen in the serum of women with benign and malignant breast diseases. - Borchert, G. H. (Nature Publishing Group, 1997)
Using a highly sensitive immunofluorometric procedure, we measured the total prostate-specific antigen (PSA) concentration in 632 sera obtained from female blood donors and women with idiopathic hirsutism, breast cancer or benign breast diseases. A total of 50 sera with total PSA > 15 ng l(-1) were fractionated by high-performance liquid chromatography (HPLC) in order to resolve the two immunoreactive molecular forms, i.e. free PSA (approximately 30 kDa) and PSA bound to alpha1-antichymotrypsin (PSA-ACT, 100 kDa). We found that breast cancer patients have presurgical serum total PSA levels similar to those of blood donors. Total serum PSA concentration decreases with age in women with idiopathic hirsutism, in cancer patients and in patients with benign breast diseases. The major molecular form of PSA in the serum of all normal and hirsute women (n = 15) is PSA bound to the proteinase inhibitor alpha1-antichymotrypsin. The major molecular form in 44% of presurgical cancer patient sera is free PSA. A total of 58% of benign breast disease patients also have in their serum mainly free PSA. We conclude that about half the patients with breast cancer or benign breast diseases have free PSA as the major molecular form in their serum, whereas patients without breast pathologies (normal blood donors, idiopathic hirsutism) have PSA bound to alpha1-antichymotrypsin as the major molecular form. The ratio of PSA/PSA-ACT may have value as a simple biochemical test for diagnosis of breast pathologies including breast cancer.